23. THE CORRELATION BETWEEN BODY CONSTITUTION AND SOME HYPERTENSION READINGS IN PEOPLE WITH HIGH BLOOD PRESSURE (Vietnam Journal of Community Medicine, 2022)
Background: Detecting the body constitution of people with high blood pressure contributes todiagnosing and treating the disease. However, the correlation between the body constitution andhypertension readings is often ignored.Objectives: To analyze the characteristics of the body constitution and assess some factors related tothe body constitution of high blood pressure patients.Subjects and methods: A descriptive cross-sectional study with an analysis of 388 patients over 18years old and diagnosed with primary high blood pressure at the Hospital of Traditional Medicine inHo Chi Minh City from Mar.2022 to Sep. 2022.Results: There is a strong correlation between the body constitution and the hypertension reading,BMI (p < 0,05); The phlegm dampness constitution and systolic blood pressure are also correlated(p < 0,05).Conclusion: Detecting the right body constitution will help the diagnosis and treatment be moreeffective.
Keywords: High blood pressure, traditional medicine body constitution.